2003
DOI: 10.1016/s0002-9440(10)63559-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Metallothionein 1 and 2 Isoforms in Breast Cancer Lines with Different Invasive Potential

Abstract: Metallothionein (MT), a low-molecular weight protein with pleiotropic functions, is believed to play an important role in tumorigenesis. The aim of this study was to compare the expression of functional MT-1 and MT-2 mRNA isoforms in five breast cancer cell lines ranging from noninvasive MCF7 breast cancer cells to highly aggressive MDA-MB-231 breast cancer cells together with breast myoepithelial cells in vitro by conventional semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
2
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
0
47
2
8
Order By: Relevance
“…27 However, we did not find such a correlation. In contrast, MDA-MB-231 cells, the most invasive line in our study, exhibited the lowest level of PCho among the cancer cell-lines whereas T47D cells, which exhibit low tumorigenicity and are non metastatic when implanted in immunodeficiency mice, 70,71 showed the highest PCho level. In addition, the concentrations of PCho reported by Aboagye and Bhujwalla differed from those obtained by us based on NTP concentration of approximately 4 mM.…”
Section: Discussioncontrasting
confidence: 65%
“…27 However, we did not find such a correlation. In contrast, MDA-MB-231 cells, the most invasive line in our study, exhibited the lowest level of PCho among the cancer cell-lines whereas T47D cells, which exhibit low tumorigenicity and are non metastatic when implanted in immunodeficiency mice, 70,71 showed the highest PCho level. In addition, the concentrations of PCho reported by Aboagye and Bhujwalla differed from those obtained by us based on NTP concentration of approximately 4 mM.…”
Section: Discussioncontrasting
confidence: 65%
“…Although metatypic BCC is regarded as an aggressive subtype of BCC, it manifested the lowest MT-I/II expression of the analyzed subtypes. We used IHC techniques to determine MT-I/II expression, but recent studies have shown that only particular MT-I/II isoforms may contribute to cancer cell aggressiveness in some tumor types [31][32][33][34][35]. In our study, we noted the highest Ki-67 antigen expression in this subtype.…”
Section: Discussionmentioning
confidence: 55%
“…An inverse relationship between the expression of MTs and PLU-1/JARID1B is also seen in breast cancer cell lines. Thus, high levels of the MTs MT1E and MT2A are found in the breast cancer cell lines Hs578T and MDA-MB-231, which express low levels of PLU-1, while lessinvasive estrogen receptor (ER)-positive cell lines, such as MCF7, ZR75, and T47D, show low expression levels of the MT proteins but high levels of PLU-1/JARID1B (3,4,46,74).…”
Section: Discussionmentioning
confidence: 99%